Prevalence of Toxoplasmosis in Blood Donors: A Systematic Review and Meta-Analysis - Amna Iqbal Butt; Ammara Riaz; Fariha Salman; Laila Afzal; Sana Qanber Abbasi; Rabiah Mahwish (Pakistan Journal of Medicine and Dentistry)
Background: Toxoplasmosis is a prevalent public health problem that infects humans and animals. Humans can become infected by consuming improperly washed vegetables, raw meat, contaminated water, or exposure to cats or their feces. Infection can also occur through transfusion of contaminated blood. The current review aimed to assess the seroprevalence of Toxoplasmosis in blood donors globally.